How has technology been used to deliver cardiac rehabilitation during the COVID-19 pandemic? An international cross-sectional survey of healthcare professionals conducted by the BACPR. Issue 4 (20th April 2021) - O'Doherty, Alasdair F; Humphreys, Helen; Dawkes, Susan; Cowie, Aynsley; Hinton, Sally; Brubaker, Peter H; Butler, Tom; Nichols, Simon
Abstract : Objective: To investigate whether exercise-based cardiac rehabilitation services continued during the COVID-19 pandemic and how technology has been used to deliver home-based cardiac rehabilitation. Design: A mixed methods survey including questions about exercise-based cardiac rehabilitation service provision, programme diversity, patient complexity, technology use, barriers to using technology, and safety. Setting: International survey of exercise-based cardiac rehabilitation programmes. Participants: Healthcare professionals working in exercise-based cardiac rehabilitation programmes worldwide. Main outcome measures: The proportion of programmes that continued providing exercise-based cardiac rehabilitation and which technologies had been used to deliver home-based cardiac rehabilitation. Results: Three hundred and thirty eligible responses were received; 89.7% were from the UK. Approximately half (49.3%) of respondents reported that cardiac rehabilitation programmes were suspended due to COVID-19. Of programmes that continued, 25.8% used technology before the COVID-19 pandemic. Programmes typically started using technology within 19 days of COVID-19 becoming a pandemic. 48.8% did not provide cardiac rehabilitation to high-risk patients, telephone was most commonly used to deliver cardiac rehabilitation, and some centres used sophisticated technology such as teleconferencing. Conclusions: The rapid adoption of technology into standard practice is promising and may improve access to, and participation in, exercise-based cardiac rehabilitation beyond COVID-19. However, the exclusion of certain patient groups and programme suspension could worsen clinical symptoms and well-being, and increase hospital admissions. Refinement of current practices, with a focus on improving inclusivity and addressing safety concerns around exercise support to high-risk patients, may be needed.